Breed, Coat Color, and Hair Length as Risk Factors for Hyperthyroidism in Cats. (13th June 2017) - Crossley, V.J.; Debnath, A.; Chang, Y.M.; Fowkes, R.C.; Elliott, J.; Syme, H.M.
Abstract : Background: Hyperthyroidism is very common in older cats, but the etiopathogenesis is poorly understood. Decreased risk of hyperthyroidism has been reported in certain colorpoint breeds, and this observation previously has been hypothesized to result from relatively greater tyrosine availability for thyroid hormone production because of limited ability to convert tyrosine to melanin pigment. However, studies investigating a potential link between coat pigmentation and risk of hyperthyroidism are limited. Objective: To identify associations between coat phenotype and hyperthyroidism by investigation of breed, coat color, and hair length as risk factors for the disease. Animals: Data were used from 4, 705 cats aged ≥10 years, referred to a single veterinary teaching hospital (2006–2014) in the United Kingdom. Methods: Retrospective, epidemiological, cross‐sectional study using Bayesian multivariable logistic regression to assess risk factors for hyperthyroidism. Results: Burmese (odds ratio [OR], 0.01; 0.00–0.23; P = .004), Tonkinese (OR, 0.05; 0.00–0.95; P = .046), Persian (OR, 0.21; 0.10–0.44; P < .001), Siamese (OR, 0.27; 0.12–0.61; P = .002), Abyssinian (OR, 0.04; 0.00–0.74; P = .031), and British shorthair (OR, 0.47; 0.28–0.79; P = .004) breeds had decreased risk of hyperthyroidism compared to domestic shorthairs. Longhaired, nonpurebred cats (OR, 1.30; 1.03–1.64; P = .028) were at increased risk of hyperthyroidism. Coat color/pattern was not associated with hyperthyroidism in nonpurebred cats. Conclusions and Clinical Importance: We identified decreased risk of hyperthyroidism in the Tonkinese, Abyssinian, and British shorthair breeds, identified an association between risk of hyperthyroidism and hair length, and confirmed decreased risk in Burmese, Siamese, and Persian breeds. Additional studies are warranted to further investigate these findings.